DESIGN AND IMPLEMENTATION OF ELECTRICAL SISTEMS FOR BREAD DOUGH DEVELOPMENT PROOFER TECHNOLOGYS BASED ON MICROCONTROLLER WITH PID CONTROL FOR DONUT DOUGH - Silviana W, Ika; Hakim, Muhammad Syaiful; Sampurno, Bambang; Nurhadi, Hendro; Mashuri, Mashuri (IPTEK The Journal of Engineering, 2025)
The proofing process is an essential step in bread-making, where the dough is allowed to rest for the gas content to develop and form a soft structure. However, many small-scale bread producers still rely on manual methods for proofing, leading to unstable temperature and humidity levels and longer production times. This study focuses on developing an electrical system for a bread proofer that can stabilize temperature and humidity during the proofing process. The system includes an Arduino Mega microcontroller with a DHT22 sensor for real-time temperature and humidity detection, an I2C LCD for monitoring, and a potentiometer for setting the desired temperature and humidity values. To achieve stability, a PID control system is used. The results show that the system can stabilize at a temperature of 40.10oC and humidity at 80-90RH for approximately 38.4 minutes. This electrical system offers an effective solution for optimizing the proofing process in bread production.